BMI trajectories are associated with NAFLD and advanced fibrosis via aging-inflammation mediation - Haiyang Peng; Zhibo Zhao; Jianping Gong; Kun He (BMC Public Health)
Abstract Background As the global epidemic of obesity fuels metabolic conditions, the burden of nonalcoholic fatty liver disease (NAFLD) will become enormous. Abundant studies revealed the association between high body mass index (BMI) and NAFLD but overlooked the BMI patterns across life stages. We aimed to explore how BMI trajectories over age relate to NAFLD. Methods Selecting 3212 participants in NHANES 2017–2020, we tracked BMI records at different ages. Using a latent class trajectory model (LCTM), we identified BMI trajectories over age. Multinomial logistic regression assessed their association with NAFLD and advanced fibrosis. Structural equation modeling (SEM) revealed mediation effects. Results We identified 3 BMI trajectories: Steady Progression, Increase to Decrease, and Rapid Ascending. There was no significant difference in NAFLD/advanced fibrosis risk between the increase-to-decrease group and the steady progression group. The Rapid Ascending trajectory significantly correlated with NAFLD (OR = 2.21, 95% CI 1.29–3.77) and advanced fibrosis (OR = 3.04, 95% CI 1.13–8.22). This association was influenced by a chain-mediated process of phenotypic age and C-reactive protein (mediated effect to NAFLD = 0.010, p < 0.01; mediated effect to advanced fibrosis = 0.003, p < 0.05). This mediation on NAFLD was independent of insulin resistance (IR). The association between rapid ascending trajectory and advanced fibrosis was more pronounced among the male subgroup (p for interaction = 0.008). Conclusion The rapid ascending trajectory of BMI correlates with an increased susceptibility to NAFLD and advanced fibrosis independent of BMI, mediated by aging and inflammation. Our results suggest that long-term maintenance of BMI is pivotal in NAFLD prevention. Aging-inflammation may represent a distinct mechanism of sustained obesity to NAFLD, independent of IR.